Recent advances in computational terminology - Bourigault, Didier; Jacquemin, Christian; L'Homme, Marie-Claude (Natural language processing (Amsterdam, Netherlands) ;, 2001)
This first collection of selected articles from researchers in automatic analysis, storage, and use of terminology, and specialists in applied linguistics, computational linguistics, information retrieval, and artificial intelligence offers new insights on computational terminology. The recent needs for intelligent information access, automatic query translation, cross-lingual information retrieval, knowledge management, and document handling have led practitioners and engineers to focus on automated term handling. This book offers new perspectives on their expectations. It will be of interest.